Kepemimpinan Instruksional Kepala Sekolah dalam Mendukung Optimalisasi Pembelajaran ICT di Madrasah Ibtidaiyah PAS Baitul Qurán Ponorogo - Diarko, Berxy; Sulton, Sulton (Universitas Muhammadiyah Ponorogo, 2026)
Instructional Leadership of School Principals in Supporting the Optimization of ICT Learning at Madrasah Ibtidaiyah PAS Baitul Qur'an Ponorogo. Instructional leadership at the Baitul Qur'an Islamic Elementary School (Madrasah Ibtidaiyah PAS) plays a vital role as a catalyst in the integration of Information and Communication Technology (ICT), which focuses not only on technical skills but also aligns with the strengthening of civic education values. Through a qualitative descriptive approach, it was found that the principal plays an active role in providing digital infrastructure, supporting teacher professional development, and creating a climate of innovation that allows technology to be used as a means of developing good citizenship. The implementation of ICT at this school is aimed at fostering awareness of digital rights and obligations, strengthening the spirit of nationalism amidst the global flow of information, and developing critical thinking skills in filtering information to maintain social integrity. Thus, effective instructional leadership at the Baitul Qur'an Islamic Elementary School (Madrasah Ibtidaiyah PAS) successfully combines technological advancements with the mission of civic education, ensuring that the digitalization of education can produce a generation that is digitally savvy but still possesses a high level of moral responsibility and loyalty to the nation and state.